Third sector organisations in the changing welfare systems of Central and Eastern European countries - Kolarič, Zinka (Teorija in praksa, 2009)
Two theoretical/methodological shifts are necessary in the research approach to third sector organisations if we want to not only identify but also explain the changes/trends seen in the development of third sector organisations in Central and Eastern European societies. The first one is a shift away from the concept of the welfare state/welfare state regime to the concept of the welfare system/type of welfare system. Realisation of this concept enables us to move beyond the isolated investigation of third sector organisations; it directs us to research third sector organisations as an important structural element of the welfare system in relation to other structural elements. The second methodological shift is a shift from convergence research to research of the diversity of the changing welfare systems of Central and Eastern European societies. This diversity is conditioned by the different socio-political strategies used by national actors as reform strategies for entire welfare systems or parts of them. These strategies determine the changes in the structure of welfare systems and thereby the position, character and role of third sector organisations as an important structural element of them.
Keywords: Nevladne organizacije; Nongovernmental organizations; Država blaginje; Welfare state; Central Europe; Srednja Evropa; Vzhodna Evropa; Eastern Europe